Structural Health Monitoring & Damage Detection, Volume 7 : Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics 2017 /: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics 2017. (2017) - Unknown
No abstract available